THE DETECTION OF EPIDEMIC SUBTYPES OF BEIJING GENOTYPE OF MYCOBACTERIUM TUBERCULOSIS CIRCULATED IN THE PRIMORSKY KRAI - P. A. Khromova; M. S. Kornilov; S. N. Zhdanova; A. A. Yakovlev; O. B. Ogarkov (Acta Biomedica Scientifica, 2018)
Background. The Far East is the territory with high rate of incidence and prevalence of tuberculosis. Cases of tuberculosis caused by epidemic strains have high frequency of MDR and XDR. It is important to study the prevalence of TB in areas with a high burden of infection, to which the Far East belongs. The aim of the research is to carry out genotyping of strains and assess the prevalence of CC1 and CC2 subtypes in the territory of Primorsky Krai. Materials and methods. The DNAs of 99 clinical isolates of MBT from Primorsky Krai have been genotyped by the 24-locus MIRU-VNTR and RD105/RD207. Results. The dominant number of strains pertained to Beijing genotype (59.6 %). The express method revealed 22 isolates of the CC2/W148 subtype, which had 6 different MIRU-VNTR-24 profile. According to MLVA classification MtbC 15-9, the most common among the isolates of CC2/W148 profile is 100-32 (59.1 %). Among these profiles the highest frequency of MDR/XDR was recorded – 69,2 %. According to the results of the express analysis, 39 isolates with 26 different MIRU-VNTR-24 profiles belonged to the CC1 subtype, of which the dominant number belonged to 99-32 and 94-32. Conclusions. The methods of express genotyping of epidemic subtypes of the Beijing genotype are very important for epidemiological surveillance and clinical practice. The developed methods allow to define a wider range of strains than previously used methods.